1997
DOI: 10.1046/j.1365-2141.1997.4953299.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe erythrocyte adenylate kinase deficiency due to homozygous A → G substitution at codon 164 of human AK1 gene associated with chronic haemolytic anaemia

Abstract: Summary.A child of Italian origin with a congenital haemolytic anaemia had spectrophotometrically undetectable erythrocyte adenylate kinase (AK) activity. Her parents and brother had approximately 50% normal AK activity, and AK electrophoresis of red blood cell (RBC) crude extract on cellulose acetate strips showed the presence of the normal allele AK1-1. No AK band was detected in the AK electrophoresis of the proband, in whom the erythrocyte 2,3-diphosphoglycerate (2,3DPG) and glutathione (GSH) concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Conversely, patients with residual red cell AK activity that was only partially reduced (from 20% to 50% of normal) exhibit a mild to moderate hemolytic anemia but normal physical and mental development. 5,6,8 The finding by Beutler et al 4 of a child with total absence of RBC AK activity and no evidence of hemolysis or mental retardation raised a question regarding the cause-effect relationship between AK deficiency and hemolytic anemia. Some investigators suggested that the shortened survival of AK-deficient RBCs was caused, or at least enhanced, by the coexistence of defects of other enzymes such as phosphoribosyl pyrophosphate synthetase, pyruvate kinase, and AMP-guanosine triphosphate (GTP) phosphotransferase 6 ; glucose-6-phosphate dehydrogenase (G6PD) 1,7 ; or other unidentified factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, patients with residual red cell AK activity that was only partially reduced (from 20% to 50% of normal) exhibit a mild to moderate hemolytic anemia but normal physical and mental development. 5,6,8 The finding by Beutler et al 4 of a child with total absence of RBC AK activity and no evidence of hemolysis or mental retardation raised a question regarding the cause-effect relationship between AK deficiency and hemolytic anemia. Some investigators suggested that the shortened survival of AK-deficient RBCs was caused, or at least enhanced, by the coexistence of defects of other enzymes such as phosphoribosyl pyrophosphate synthetase, pyruvate kinase, and AMP-guanosine triphosphate (GTP) phosphotransferase 6 ; glucose-6-phosphate dehydrogenase (G6PD) 1,7 ; or other unidentified factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although in this case the neurologic impairment was attributed to the forceps delivery and resuscitation at birth, mental retardation from mild to severe has been later reported in other patients with severe red cell AK deficiency. [7][8][9] Since the AK1 isoenzyme is expressed in red cells and brain, it can be suggested that the mutation, especially in such cases of severe enzyme deficiency, may be accompanied by brain abnormalities. Conversely, patients with residual red cell AK activity that was only partially reduced (from 20% to 50% of normal) exhibit a mild to moderate hemolytic anemia but normal physical and mental development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal conditions, AK 1-knockout mice showed no phenotypic changes. However, under metabolic stress, compromised energetics were detected in the heart and skeletal muscle, suggesting the physiological significance of AK-catalysed phosphoryl transfer between the intracellular compartments in cellular energetic homoeostasis (Qualtieri et al 1997;Janssen et al 2001). The nucleoside analogues of AK have been used clinically for treating certain viral infections and malignant diseases (Pucar et al 2000;Bourdais et al 1996;Schneider et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Both 491G and 382T are located in the exon 6 of AK1 gene, suggesting that this region encodes crucial amino acid residues. 47) Recently, a nonsense mutation at colon 107, 319CGA -~ TGA, of the AK1 gene has been revealed in two siblings of Italian origin.48) The proband showed mild chronic hemolytic anemia as well as psychomotor impairment. The mutation causes truncation of the AK1 polypeptide, resulting in complete loss of AK1 activity in the affected RBC.…”
mentioning
confidence: 99%